2014
DOI: 10.1111/ijpp.12154
|View full text |Cite
|
Sign up to set email alerts
|

‘Because of the circumstances, we cannot develop our role’: Norwegian community pharmacists’ perceived responsibility in role development

Abstract: There is a gap between what the Norwegian community pharmacists express as their vision and current practice. The identified agent relationships appear to hamper the pharmacists' perceived ability to be active and take full responsibility in their role development and further implementation of patient-centred care. Adopting a fairly inactive position when it comes to increasing patient-centred care might be a result of a traditional product-focused pharmacy culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Norwegian community pharmacists are by law required to give patients information about the drugs upon dispensing and confirm that the patient understands how to use them [14]. On the other hand, they admit that this part of their work is only performed to a certain extent [15]. A recent focus group study showed that the main reason for this is that they are given too many other tasks related to sales by the head office and thereby feel that they are always short of time [15].…”
Section: Introductionmentioning
confidence: 99%
“…Norwegian community pharmacists are by law required to give patients information about the drugs upon dispensing and confirm that the patient understands how to use them [14]. On the other hand, they admit that this part of their work is only performed to a certain extent [15]. A recent focus group study showed that the main reason for this is that they are given too many other tasks related to sales by the head office and thereby feel that they are always short of time [15].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Nevertheless, pharmacists and pharmacy employers report a need for an increased focus on clinical training in the pharmacy curriculum, including more training in patient communication skills. [16][17][18][19][20] In another study, Nordic course leaders were surveyed on the current training practice and their opinions regarding teaching of patient communication skills in Nordic pharmacy schools. 21 The course leaders reported a need for increased training.…”
mentioning
confidence: 99%
“…However, the results show that pharmacists themselves do not seem to take the lead either. Tendencies in this direction have also been shown in Norway, where there is also a pharmacy market with liberal owner regulations [26]. The consequences of these disengaged attitudes could have a detrimental effect on community pharmacists as healthcare workers, and, in the end, affect patient outcomes negatively.…”
Section: Discussionmentioning
confidence: 99%